Effect of different levels of NPK on yield and yield attributes of water melon (Citrullus lanatus Thunb.) (Indian Journal of Arid Horticulture, 2016)
An investigation was carried out to study the effect of different levels of NPK on fruit yield and yield attributes ofwatermelon. The treatments studied were T1 (50 kg N, 35 kg P2Os, 50 kg K2O), T2 (60 kg N, 40 kg P2Os, 60 kg K2O), T3 (70kg N, 45 kg P2Os, 70 kg K2O), T4 (80 kg N, 50 kg P2Os, 80 kg K2O), Ts (90 kg N, 55kg P2Os, 90 kg K2O),T6 (100 kg N, 60kg P2Os, 100kg K2O) and a control without fertilizer application (T 7 ) which were replicated three times. The result of thestudy revealed that the yield and yield attributing characters of watermelon were significantly affected by the differenttreatments tested. The treatment Ts produced significantly the highest 35.77 t/ha fruit yield while control plant produced thelowest fruit yield 8.64 t/ha and also it was superior over other treatments in term of number of female flower/vine (14.50),fruit diameter (22.49 cm), Flesh thickness (19.75 cm ), Flesh to rind ratio (2.99), Fruit dry weight (1144.80 g) /vine,Biological yield (1638.30g), Harvest Index (69.88%) and total sugar content of the fruit ( 7.62 %). Therefore, the Ts with90:55:90 kg NPK /ha could be suggested as the optimum fertilizer dose for maximizing yield and its attributes of watermelonvariety sugar Baby for agro-climatic condition of Assam.
Keywords: Fertilizer dose; Yield; Harvest Index; Flesh to Rind ratio; Watermelon